Voltage Stability Index Improvement In Radial Distribution Systems Using Capacitors - Doni, Donata; Gianto, Rudy; Abidin, Zainal (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2024)
The radial distribution network system is an important part of the electric power system because this distribution system is useful for distributing electricity to loads (customers). the existence of voltage drops and electric power losses in the provision of electrical energy is something that cannot be avoided. There are several ways that can be done to improve voltage, one of which is the installation of Shunt capacitors in the primary distribution network. Voltage drop can occur in the power system due to the loss of voltage stability in the radial distribution network. This study analyzes the value of voltage stability index in 33-bus IEEE and 69-bus IEEE with current injection method power flow analysis. In the 33-bus IEEE system, the existing condition obtained the minimum bus voltage of 0.9131 pu or 11.560 kV occurs at bus-18. By installing 2 units of shunt capacitors in the 33-bus IEEE system, it can minimize active power losses from 202.464 kW to 157.153 kW or by 22.38%.   In the existing 69-bus IEEE system, the minimum bus voltage of 0.9092 pu or 11.511 kV occurs at bus-65. With the installation of 1 unit of shunt capacitor, the voltage at the installation of 3 units of shunt capacitors, the voltage at bus-65 is 0.9514 pu or 12.045 kV, which has increased by 0.534 kV. By installing 3 units of shunt capacitors in the 69-bus IEEE system, it can minimize active power losses from 224.698 kW to 22.994 kW or by 5.21%..